ANALYSIS ON THE PERFORMANCE OF PUBLIC ADMINISTRATION IN THE IMPLEMENTATION OF URBAN SIGNAGE POLICIES (CIPEEX, 2022)
IT IS UNDERSTOOD AS SIGNALING AND INSPECTION ACTS PERFORMED IN ORDER TO MAINTAIN ROAD SAFETY. THE 1988 FEDERAL CONSTITUTION ESTABLISHES SEVERAL RIGHTS FOR CITIZENS, ONE OF THEM IS THE RIGHT TO RECEIVE INFORMATION ABOUT PUBLIC AGENCIES, REGARDLESS OF WHETHER SUCH INFORMATION IS OF PERSONAL, COLLECTIVE AND GENERAL INTEREST, IN ADDITION TO ADMINISTRATIVE ACTS AND RECORDS OF THE GOVERNMENT ITSELF. IN THIS SENSE, THE PRESENT WORK HAS AS ITS GENERAL OBJECTIVE TO ANALYZE THE OMISSION OF THE PUBLIC ADMINISTRATION REGARDING THE IMPLEMENTATION OF SIGNALING AND MONITORING WITHIN THE TRANSPARENCY LAW. BEING MORE OBJECTIVE AND WITH THE INTENTION OF REGULATING AND EXPLAINING, THE TRANSPARENCY LAW WAS CREATED (COMPLEMENTARY LAW 131/2009), WITH THIS INTENTION OF GUARANTEEING TO THOSE INVOLVED WHAT MUST BE DONE AND IN CERTAIN CASES. THE SCOPE OF THE LAW IS QUITE LARGE, MAKING IT CLEAR TO ALL BODIES THAT THEY NEED TO COMPLY WITH IT. TECHNOLOGY ALLOWS THIS TO BE DONE EVEN WITH A CERTAIN EASE. IN FACT, THE FOLLOWING QUESTION CORROBORATED THE GUIDING PROBLEM OF THIS STUDY: HOW CAN WE DEMAND FROM THE MUNICIPAL TRANSIT AUTHORITY THE RENDERING OF ACCOUNTS, WITH ALL THE EXPENSES MADE WITH MATERIALS AND EQUIPMENT FOR INSPECTION OR CITY SIGNALING? FOR THIS, IT IS UP TO THE PUBLIC ADMINISTRATION TO DEVELOP AND APPLY MANAGEMENT SYSTEMS TO BE ABLE TO MAKE THIS DISCLOSURE IN AN INTELLIGENT AND EFFICIENT WAY. FORTUNATELY, TECHNOLOGY ALLOWS THIS TO BE DONE EVEN WITH A CERTAIN EASE. THIS STUDY FINDS A HIGH DEGREE OF IMPORTANCE IN THE LEGAL, SCIENTIFIC AND SOCIAL SPHERES, BECAUSE IT AIMS TO ADDRESS THE CITIZEN'S KNOWLEDGE ABOUT THE TRANSPARENCY LAW, A SUBJECT EXPLORED FEW TIMES AND OF SUCH IMPORTANCE, IF WE DO NOT HAVE SIMPLE AND CLEAR READING ACCESS TO THIS INFORMATION, BEARING IN MIND THAT IT IS THE DUTY OF THE PUBLIC ADMINISTRATION TO MAKE THIS INFORMATION REACH CITIZENS IN A VERY CLEAR WAY. THE TEXT OF THE LAW EXPLAINS THIS VERY CLEARLY ACCORDING TO ART. 5 OF THE ACCESS TO INFORMATION LAW (LAW NO.&NBSP; 2.527/2011) BRINGING SCIENTIFIC AND INFORMATIVE CONTRIBUTIONS TO THE POPULATION, INCLUDING BEING ABLE TO BE THE SUBJECT OF LEGISLATIVE PROPOSAL. THUS, IT IS IMPORTANT TO ADDRESS THE PROPOSED THEME, SINCE THE RESULTS OBTAINED POINT TO THE ABSENCE OF TRANSPARENCY OF WORKS THAT OCCUR IN OUR CITY, VIOLATING THE LAW SET FORTH IN THE CONSTITUTION PROVIDED IN THE FEDERAL CONSTITUTION.
Keywords: Public Administration; Federal Constitution; Complementary Law